Structure-function analysis of CNGA3-associated achromatopsia patient variants complements clinical genomics in pathogenicity determination - Ditte K. Rasmussen; Young Joo Sun; Joel A. Franco; Aarushi Kumar; Jennifer T. Vu; Alexander G. Bassuk; Vinit B. Mahajan (Orphanet Journal of Rare Diseases)
Abstract Background Achromatopsia is an autosomal recessive genetic disease, and 95% of achromatopsia patients carry pathogenic mutations in the CNGA3 and CNGB3 genes. Once translated, these genes function together by forming a cone photoreceptor CNG channel protein complex. Results There are 150 CNGA3 missense variants reported in achromatopsia patients, but the pathogenicity of 103 variants remains unknown due to inconclusive genetic information. Here, we present clinical features of a novel CNGA3 variant in an achromatopsia patient and demonstrate its pathogenicity by a three-dimensional (3D) proteoform-based structure-function analysis. We first identified six proteotypic groups using 47 pathogenic missense variants with distinctive functional consequences by mapping their spatial proximity in a 3D protein structure. This meta-analysis was further applied to 103 missense variants of unknown significance (VUS) found in patients with achromatopsia. Strikingly, 86.4% of VUS had similar/identical functional consequence to nearby pathogenic variants, which suggested their likely pathogenicity and potential molecular pathology. The distinct proteotypic consequence of CNGA3 mutants shown in our analysis strongly supported the notion that gene supplementation may be the most widely applicable therapeutic option for CNGA3-associated achromatopsia patients. Conclusion Thus, proteoform-based analysis can be a valuable approach for assessing novel variants and complement clinical genomics in its utilization.